Adequacy and Application of Models of Cognizing by Combinatorial Games - Grigoryan, Sedrak V.; Naghashyan, Zaven H. (Mathematical Problems of Computer Science, 2024)
We aim to provide constructive adequate models of human cognizing of the Universe. Arguing that combinatorial games are adequate models for studying humanuniverse problem, we introduce a class of Reproducible Game Trees (RGT) combinatorial games, generally, not limited in the representation of competitive, defense and communication problems. We develop expert knowledge-based RGT Solver for unified searching of plausible RGT strategies arguing that such strategies are transferable to the entire RGT class. We estimate the adequacy of models of cognizing, particularly, by progressing in solving RGT problems, which simultaneously provide solutions for urgent applications. In this work, we outline our RGT approach to arguing the adequacy of cognizing models to the human one and bring together successful applications induced by such arguing.